Healthbuddy: Your personal health companion - Tan, Yuan Seng (2025)
HealthBuddy: Your Personal Health Buddy is a health mobile application for smart phones designed to respond to the growing demand for holistic and personalized healthcare management solutions. The project was initiated to address the fragmentation of healthcare monitoring technologies, which inevitably results in wastage and decreasing user engagement. The proposed solution integrates different aspects of health into a single simple-to-use interface. The design features a Health Dashboard for tracking such measurements as weight, height and summary of their health details from other features, Medication and Appointment Reminders, Hydration Checks, and a Nutrition Planner recommending food options by input designated calorie intake. A mental health support chatbot utilizing artificial intelligence is proposed to offer mood tracking and stress management functionality and giving unconditionally support by understanding user’s requirement. Besides, Health and Fitness Challenges will be implemented to encourage user engagement through a reward system, and an Emergency Assistance is coded to provide immediate support in case of serious health events. Currently, the development is in prototyping of the features to determine their feasibility and user flow. By consolidating physical as well as mental well-being support under a single platform, HealthBuddy aims to provide the best possible service among the mobile health (mHealth) technologies.